Apoptosis and turnover disruption of olfactory sensory neurons in eosinophilic chronic rhinosinusitis - Chen, Yuetong; Li, Minghan; Lu, Juan (Frontiers in Cellular Neuroscience, 2024)
Olfactory dysfunction is one of important and difficult-to-treat symptoms of eosinophilic chronic rhinosinusitis, which is typically associated with type 2 inflammation where eosinophils function as both effector and initiator. Eosinophilic infiltration in olfactory mucosa is associated with severer olfactory dysfunction and mucosal erosion, more loss of olfactory sensory neurons (OSNs). Active eosinophils derived cytokines, chemokines and eosinophil granule proteins may lead to aggravation of inflammation, tissue damage, survival and regeneration of OSNs. Recent studies show that EOSs can lead to apoptosis of OSNs through axonal and neural body damage, turnover disorder of OSNs through number loss of immature OSNs and GBCs, and changed proliferative activity of HBCs, and dysfunction of OSNs through breakdown of neuroepithelial integrity and alteration of ion concentration in OSNs and mucin. In this review, we outline the current progress on the role of eosinophils on the olfactory dysfunction in patients with eosinophilic chronic rhinosinusitis and mechanism of eosinophils associated injury of olfactory mucosa and OSNs in experimental animal model with sinonasal inflammation. Further investigations on the molecular mechanisms of tissue eosinophilia induced injury of OSNs are warranted to obtain new therapeutic target and achieve better restoration of olfactory function.